2016
DOI: 10.3233/jpd-150750
|View full text |Cite
|
Sign up to set email alerts
|

Slowness in Movement Initiation is Associated with Proactive Inhibitory Network Dysfunction in Parkinson’s Disease

Abstract: These results provide physiological data consistent with impaired control of proactive inhibition over motor initiation in PD. Patients would be locked into a mode of control maintaining anticipated inhibition over willed movements even when the situation does not require action restraint. The functional and neurochemical bases of brain activity associated with executive settings need to be addressed thoroughly in future studies to better understand disabling symptoms that have few therapeutic options like aki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 51 publications
2
27
0
Order By: Relevance
“…Our results revealed abnormal proactive inhibition in the drug-treated patients and surgical patients with GPi-DBS off compared to the healthy controls. This is consistent with previous studies, which indicated proactive inhibition might be endogenously impaired in PD patients as a result of specific hypoactivation of a proactive inhibitory network ( Criaud et al, 2016 ). However, a mixed effect of medications and PD pathology would be a more reasonable interpretation of the results, as all the participants were using medication and robust evidence has confirmed the role of Parkinson’s medications in inhibitory control ( Voon et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our results revealed abnormal proactive inhibition in the drug-treated patients and surgical patients with GPi-DBS off compared to the healthy controls. This is consistent with previous studies, which indicated proactive inhibition might be endogenously impaired in PD patients as a result of specific hypoactivation of a proactive inhibitory network ( Criaud et al, 2016 ). However, a mixed effect of medications and PD pathology would be a more reasonable interpretation of the results, as all the participants were using medication and robust evidence has confirmed the role of Parkinson’s medications in inhibitory control ( Voon et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…) and related disorders in PD (Criaud et al . ). Second, these changes are observed in the critical alpha band, which indexes an active inhibitory mechanism relying on rhythmic local fluctuations of GABAergic inhibitory interneurons (Lőrincz et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Criaud et al . ). This executive disorder concerns proactive inhibition, a function which is intended to inhibit movement triggering mechanisms in the absence of stimulation in uncertain environments.…”
mentioning
confidence: 97%
See 2 more Smart Citations